The Influence of Climatic Factors on The Biometric Indicators of Carrots - Abdullayev Ilkhom Eshkurbanovich (Scientific Trends, 2023)
This article presents the results of tests of domestic and foreign varieties of table carrots in the desert soil – climatic zone of Surkhandarya region. The assessment of 22 varieties of table carrots on productivity and quality of the harvest is given.
Keywords: Table carrots, temperature, bolstering, root crop diameter, root crop length.